2020
DOI: 10.1017/wpt.2020.3
|View full text |Cite
|
Sign up to set email alerts
|

Design considerations for contact-less underwater power delivery: a systematic review and critical analysis

Abstract: Wireless power transfer (WPT) has attracted attention from academia and industry in recent years. WPT has natural electrical isolation between primary and secondary side, which ensures safe charging in an underwater environment. This breakthrough technology greatly facilitates the deep-sea power transmission. However, at the current stage the transferred power and energy efficiency level are not up to that of the WPT system in the air. The major concerns include the attenuation is seawater, extreme temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…where 𝜇 1 and 𝜇 2 are the permeabilities at temperatures 𝜃 1 and 𝜃 2 , respectively. The B-H curve initial permeability curve of ferrite at different temperatures is shown in Figure 4 , and the initial permeability curve of ferrite at different temperatures is shown in Figure 5, respectively [43]. It can be observed that ferrites have minimal effect on the actual sea water temperature range.…”
Section: Effect Of Seawater Temperature and Pressure On Wptmentioning
confidence: 94%
See 1 more Smart Citation
“…where 𝜇 1 and 𝜇 2 are the permeabilities at temperatures 𝜃 1 and 𝜃 2 , respectively. The B-H curve initial permeability curve of ferrite at different temperatures is shown in Figure 4 , and the initial permeability curve of ferrite at different temperatures is shown in Figure 5, respectively [43]. It can be observed that ferrites have minimal effect on the actual sea water temperature range.…”
Section: Effect Of Seawater Temperature and Pressure On Wptmentioning
confidence: 94%
“…This technology was first used in air medium, wireless charging pile position of electric vehicles in transportation field [23,24], pocket wireless charger of the miniature electronic pacemaker in the medical field [25,26], and wireless transmission of industrial field and smart homes [27,28]; however it has gradually been extended to seawater medium owing to advancement and high demand for this technology [29,30]. Due to the particular complexity of seawater environment, wireless power transfer is faced with serious electromagnetic wave attenuation [31,32], irregular disturbance of seawater ocean current, difficult docking of charging equipment and other problems [33,34], and its efficient transmission has not been fundamentally solved [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…MESA had designed INPUD DON series devices for deep-sea regions and INPUD CAN series devices for coastal waters as shown in Figure 25. It allows 2500 rmp rotary speed and 90% efficiency for 10 W power [134]. A Japanese TRITON company also designed a buoy system to achieve power and data transmission simultaneously.…”
Section: Ocean Observation Networkmentioning
confidence: 99%
“…IF Lopes et al [12] have discussed a maximum efficiency tracking strategy for UWPT. A systematic review and critical analysis on UWPT is presented [13]. In [14], Tamura et al have focused on some pivotal elements to improve coupling coefficients for underwater wireless power transfer (UWPT).…”
Section: Related Workmentioning
confidence: 99%